2019
DOI: 10.1038/s41598-019-41974-9
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Genes are Highly Expressed in Malignant Astrocytomas and Associated with Patient Survival

Abstract: Gliomas are heterogeneous, primary brain tumours that originate from glial cells. The main type of gliomas is astrocytomas. There are four grades (I-IV) of astrocytoma malignancy. Astrocytoma grade IV known as glioblastoma multiforme (GBM) is the most common and aggressive type of astrocytic gliomas. Metallothioneins (MT) are low molecular weight, cysteine rich proteins encoded by a family of metallothionein ( MT ) genes. MT genes play a crucial role in carcinogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…MT gene expression has been associated with glioma malignancy grade, 7 and MT3 associates with a poor patient survival. 5 , 7 We have found that the GBM U87 cell line expresses high levels of MT3 mRNA, as compared to grade II 1321N1 astrocytoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MT gene expression has been associated with glioma malignancy grade, 7 and MT3 associates with a poor patient survival. 5 , 7 We have found that the GBM U87 cell line expresses high levels of MT3 mRNA, as compared to grade II 1321N1 astrocytoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…MT gene expression has been associated with glioma malignancy grade, 7 and MT3 associates with a poor patient survival. 5 , 7 We have found that the GBM U87 cell line expresses high levels of MT3 mRNA, as compared to grade II 1321N1 astrocytoma cells. These differences are unlikely to depend on a different modulation of MT3 expression by intracellular labile zinc 36 because MT3 mRNA levels were not affected by zinc depletion and restoration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations